2022
DOI: 10.1002/admi.202200904
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Chemical Anchoring via Bidirectional Active Site Additive Enables Efficient and Stable Perovskite Solar Cells

Abstract: Since the first demonstration on all-solidstate perovskite solar cells (PSCs) with a power conversion efficiency (PCE) of 9.7%, [3] the PCE of the organometal halidebased PSCs has skyrocketed from initial 3.8% [4] to presently certified 25.7%, [5] which makes the PSCs a promising candidate for the next-generation solar cells. It is well known that efficient and stable PSCs require high quality perovskite films. However, a large number of defects exist on the surface and grain boundaries (GBs) of perovskite fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Figure 1a shows that B 12 has multiple carbonyl and amino groups, which can simultaneously passivate the various trap sites of perovskite material, such as non‐coordinating Pb 2+ and neutral iodine, leading to strong regulation of the crystallization of perovskite film with lower trap density, preventing non‐radiative recombination, and enhancing charge carrier transport [2b,26] . A change in the binding energy of the Pb and I, presented in Figure S8a–b, provided more evidence for the B 12 ‐perovskite film interaction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 1a shows that B 12 has multiple carbonyl and amino groups, which can simultaneously passivate the various trap sites of perovskite material, such as non‐coordinating Pb 2+ and neutral iodine, leading to strong regulation of the crystallization of perovskite film with lower trap density, preventing non‐radiative recombination, and enhancing charge carrier transport [2b,26] . A change in the binding energy of the Pb and I, presented in Figure S8a–b, provided more evidence for the B 12 ‐perovskite film interaction.…”
Section: Resultsmentioning
confidence: 97%
“…The built‐in potential ( V bi ) of the SnO 2 and the SnO 2 @B 12 ‐based device was further studied by measuring Mott‐Schottky curves [26] . Figure 5c shows that the V bi of that specific device is higher in comparison to that of the control device by 0.026 V, favoring the carrier separation, transport, and extraction processes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these defects are sensitive to environmental factors, such as moisture, oxygen, temperature, etc., affecting the optoelectronic properties of the perovskite, even leading to degradation. To solve these problems, many scientists have explored various strategies, such as additive engineering, [ 9 , 10 ] interface engineering, [ 11 , 12 , 13 ], and so on. Various materials with multiple functional groups have been used to assist these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The method of low-dimensional perovskite passivation 3D perovskite has positive effect of improving the efficiency and stability of PSCs. [25][26][27][28][29][30][31] Even though the quality of the perovskite films were optimized by the reported effective passivation methods, but most of the optimization are conducted by single functional, and the optimized perovskite still suffers from the corrosion of the external environment (such as high humidity) directly. Therefore, it's time to develop suitable passivators with functional groups which not only for passivated defects, but also need external protective functional groups for resistance to environmentalThe Achilles heel of the perovskite solar cells (PSCs) is the long-term stability under working condition which restricts the commercialization.…”
mentioning
confidence: 99%
“…Lewis acids and bases have been proven functional in bonding with uncoordinated halides or metal ions in the perovskite crystals to form Lewis adducts, thereby reducing the density of defects. [25][26][27] Ma et al introduced nicotinamide as a Lewis base additive into the perovskite precursor solution, which found that the nicotinamide in the perovskite film can passivate the surface and grain boundary defects, control the morphology of the film, and improve the crystallinity. [25] Wang et al evidenced that BA + can form a two-dimensional (2D) layered perovskite with a wide band gap upon the threedimensional (3D) perovskite.…”
mentioning
confidence: 99%